2011
DOI: 10.1177/008124631104100307
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Attitudes of University Students: The Role of Personality Traits and Demographic Factors

Abstract: The current study examined the influences of personality traits, gender, previous counseling or therapy experiences, and knowledge about the psychological services provided on campus on the help-seeking attitudes of Turkish undergraduate students and their initial preferences for help sources. The students ( N = 524) completed measures of attitudes toward help-seeking, personality traits, and demographic factors. Hierarchical linear regression indicated that the females, those who had knowledge about the psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 36 publications
(37 reference statements)
3
39
0
10
Order By: Relevance
“…It was found that as participants reported greater openness to new experiences, they showed more favorable attitudes toward counseling. Another study by Atik and Yalcyn (2011) revealed a similar result, to the effect that college students with higher ratings on the Openness subscale of the Big Five Inventory (Goldberg 1999) showed more positive attitudes toward counseling.…”
Section: Psychological Variables Related To Attitudes Toward F2f Counmentioning
confidence: 58%
“…It was found that as participants reported greater openness to new experiences, they showed more favorable attitudes toward counseling. Another study by Atik and Yalcyn (2011) revealed a similar result, to the effect that college students with higher ratings on the Openness subscale of the Big Five Inventory (Goldberg 1999) showed more positive attitudes toward counseling.…”
Section: Psychological Variables Related To Attitudes Toward F2f Counmentioning
confidence: 58%
“…Üniversite öğrencilerinin psikolojik yardım arama davranışlarının çeşitli yönlerden incelendiği bir başka çalışmada da öğrencilerin herhangi bir problem yaşadıklarında daha çok aile ve arkadaşlarından yardım almaya gönüllü oldukları saptanmıştır (Erkan, Özbay, Cihangir Çankaya ve Terzi, 2012b). Atik ve Yalçın (2011) ve Topkaya ve Meydan (2013 tarafından üniversite öğrencileri ile yürütülen çalışmalarda da bireyler sorunlarının çözümü için öncelikli olarak akranlarından ve ailelerinden yardım istediklerini belirtmişlerdir. Alanyazında elde edilen bulgular ile bu araştırma sonucunda elde edilen bulgular paralellik göstermektedir.…”
Section: Discussionunclassified
“…Örneğin; cinsiyet (Soorkia, Snelgar ve Swami, 2011;Şahin ve Yüksel Uyar, 2011), damgalama (Reynders, Kerkhof, Molenberghs ve Audenhove, 2014), psikolojik yardım almış aile üyesine sahip olma ve eğitim düzeyi (Rougier, 2011), daha önce psikolojik yardım almış olma (Erkan, Özbay, Cihangir Çankaya ve Terzi, 2012a;Türküm, 2005), cinsiyet rolleri (Kalkan ve Odacı, 2005;Özbay, Terzi, Erkan ve Cihangir Çankaya, 2011;Türküm, 2005), yardım arama niyeti (Roldan-Bau, 2013), dışadönüklük, uyumluluk ve yaşantılara açık olma (Atik ve Yalçın, 2011), utanç (Quach ve Hall, 2013), kendini saklama (Özbay vd., 2011), benlik kurguları ve sosyal destek (Koydemir Özden, 2010), özel bir kişiden alınan sosyal destek, aile ile yaşanan sorunlar, cinsel sorunlar ve akademik sorunlar (Erkan vd., 2012a), kişisel gelişim yönelimi ve farkındalık (Oluyinka, 2011), bağlanma stilleri ve ruminasyon (Turan ve Erdur Baker, 2014) ile ilişkili bulunmuştur. Bu çalışmalarda genel olarak; kız öğrencilerin erkek öğrencilere göre psikolojik yardım almaya ilişkin daha olumlu bir tutuma sahip oldukları, ayrıca daha önce psikolojik yardım almış olmanın veya ailesinde psikolojik destek almış olan birisinin var olmasının da psikolojik yardım arama davranışını olumlu yönde etkilediği saptanmıştır.…”
unclassified
“…Ayrıca yardıma ihtiyacı olduğu halde profesyonel yardım servislerine gelmekten çeşitli nedenlerle kaçınan utangaç (Atik ve Yalçın, 2011), nevrotik (Özdemir, 2012) Turkish Edition,3(6).…”
unclassified